Determinants of graduate unemployment: case study in Malaysia - Heng, Eeh Eeh; Ng, Yue Ying; Ngeow, Shin Yee; Siau, Bei Er (2022)
In the current era, the case of graduate unemployment (GU) keeps on increasing due to the structural changes in the labour market and mismatch happens between employers' expectations on graduates’ capability in education and employability skills compared to graduates’ actual capability and expectation on a job. Throughout the whole research, the main objective of this study is to investigate the determinants of graduate unemployment in Malaysia through employability skills (ES), quality of education (QE), job expectations (JE) and market demand (MD). It is predicted that employability skills, quality of education, job expectations and market demand have a significant relationship with graduate unemployment. The research study is conducted using quantitative research designs in terms of quasi-experimental research. It is decided to use a primary data collection method to collect data information from the respondents. There are 387 questionnaires being distributed online through snowball sampling method and the data collected is being analysed through Reliability test, Pearson Correlation Coefficient test and Multiple Linear Regression test. The result shows that there is a significant negative relationship between graduate unemployment with employability skills, quality of education and market demand while there is a significant positive relationship between graduate unemployment and job expectations. In conclusion, universities should put more effort into collaborating with the outsiders, industries, and lecturers to improve students’ exposure towards relevant skills, knowledge needed at the same time help students to build a more realistic expectation towards the working environment. Besides, the government should also take more care on the situation of graduate unemployment and adjust the minimum wages for the fresh graduates at the same time help the fresh graduates in the job searching process.